Malaysia: Intellectual Property - Azmi, Ida Madieha; Abd Jalil, Juriah; Ismail, Suzi Fadhilah (Kluwer Law International, 2013)
The monograph "Malaysia" is an integral part of Intellectual Property in the International Encyclopaedia of Laws series.